Use of intraoperative parathyroid hormone measurements during parathyroidectomy to predict postoperative parathyroid hormone levels in patients with renal hyperparathyroidism: meta-analysis. Issue 1 (15th February 2022) - van Beek, Dirk-Jan; Fredriksson, Stina; Haegele, Stefanie; Raffaelli, Marco; Riss, Philipp; Almquist, Martin
Abstract: Background: Several studies have reported on the use of intraoperative parathyroid hormone (ioPTH) measurements during parathyroidectomy (PTX) for renal hyperparathyroidism (rHPT), but there is no consensus on whether it is helpful and, if so, what protocol should be used. Therefore, the literature was systematically reviewed to assess a correlation between ioPTH and early postoperative parathyroid hormone (PTH) levels in patients undergoing PTX for rHPT, separately for those on dialysis and those with a functioning renal transplant. Methods: A systematic literature search was performed in electronic databases. Quality assessment was performed using the ﻿Quality In Prognosis Studies tool. Mean ioPTH values were calculated at different time points and correlated to the postoperative PTH levels within 1 month. Fixed-effect and random-effects models were performed to assess the mean ioPTH levels at 10 or 20 min after resection (T10 and T20). Stratified analyses were performed for patients on dialysis and those with a functioning renal transplant. Results: Of the 3087 records screened, 14 studies were included, including some 1177 patients; 1091 were on dialysis and 86 had a functioning kidney transplant. Risk of bias was moderate for most studies. For patients on dialysis, T10 and T20 mean ioPTH levels were 32.1 (95 per cent c.i. 24.3 to 39.9) pmol/l and 15.4 (95 per cent c.i. 7.8 to 22.9) pmol/l) in the random effects meta-analysis. Between individual studies, ioPTH ranged from 4.0–65.1 pmol/l at T10 and 8.6–25.7 pmol/l at T20. T10 and T20 ioPTH were 9.6 and 4.1 times the postoperative PTH—after T20 ioPTH stabilized in those on dialysis. In patients with a functioning renal transplant, ioPTH levels seemed to plateau after 10 min and measured 2.6 times the postoperative PTH. Conclusion: There is a strong correlation between ioPTH and early postoperative PTH levels, indicating that ioPTH is potentially a useful instrument during PTX in patients with rHPT. For patients on dialysis, at T20 ioPTH levels have stabilized and are approximately four times the postoperative PTH. Therefore, it is recommended to use ioPTH 20 min after resection in patients on dialysis, which might be longer than necessary for those with a kidney transplant. Abstract : Surgery for renal hyperparathyroidism is difficult—the surgeon must decide how much parathyroid tissue to remove and how much to leave behind. This systematic review and meta-analysis shows that intraoperative measurements of parathyroid hormone during parathyroidectomy for renal hyperparathyroidism can predict early parathyroid hormone levels and could therefore be useful.